2020
DOI: 10.1007/jhep10(2020)016
|View full text |Cite
|
Sign up to set email alerts
|

Two-loop rational terms in Yang-Mills theories

Abstract: Scattering amplitudes in D dimensions involve particular terms that originate from the interplay of UV poles with the (D − 4)-dimensional parts of loop numerators. Such contributions can be controlled through a finite set of process-independent rational counterterms, which make it possible to compute loop amplitudes with numerical tools that construct the loop numerators in four dimensions. Building on a recent study [1] of the general properties of two-loop rational counterterms, in this paper we investigate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(60 citation statements)
references
References 71 publications
2
55
0
Order By: Relevance
“…One-loop rational counterterms δR 1 do not depend on the choice of UV renormalisation scheme, while two-loop rational counterterms δR 2 are scheme dependent [29]. This dependence involves a trivial contribution, which corresponds to the naive renormalisation of δR 1 counterterms, plus a non-trivial scheme dependence, which is due to the fact that the multiplicative renormalisation of UV subdivergences does not commute with the projection of loop numerators to D n = 4 dimensions.…”
Section: Jhep01(2022)105mentioning
confidence: 99%
See 2 more Smart Citations
“…One-loop rational counterterms δR 1 do not depend on the choice of UV renormalisation scheme, while two-loop rational counterterms δR 2 are scheme dependent [29]. This dependence involves a trivial contribution, which corresponds to the naive renormalisation of δR 1 counterterms, plus a non-trivial scheme dependence, which is due to the fact that the multiplicative renormalisation of UV subdivergences does not commute with the projection of loop numerators to D n = 4 dimensions.…”
Section: Jhep01(2022)105mentioning
confidence: 99%
“…This method was a key ingredient for the automation of one-loop calculations, and the foundations for its extension to two loops have been established in [28,29], where it was shown that renormalised two-loop amplitudes can be constructed through a modified version of the R-operation for loop amplitudes with D n = 4 dimensional integrand numerators. In this approach, the usual one-loop and two-loop counterterms for the subtraction of UV poles are supplemented by corresponding rational counterterms, which reconstruct the contributions that arise from the interplay of UV poles with the (D − 4)-dimensional parts of loop numerators.…”
Section: Jhep01(2022)105mentioning
confidence: 99%
See 1 more Smart Citation
“…In the same spirit, but from a different point of view, interesting results have also recently been obtained on extending recursion techniques (based on Feynman diagrams!) to construct two-loop integrands efficiently starting from lower loop amplitudes [16][17][18]. These developments are very promising, and they have made it possible to compute various non-trivial amplitudes, in particular in the very special all-plus configuration [19,20].…”
Section: Obtaining the Integrandmentioning
confidence: 99%
“…We would like to remark that the method of pulling out the UV behaviour of the amplitude can be traced back to the original papers regarding the BPHZ theorem[1,[76][77][78][79], used in[86][87][88] and has recently been reconsidered in[89] 13. We point out that this procedure of extracting the UV behaviour of multi-loop scattering amplitudes, directly from the Feynman propagators, can be compared with the procedure described in Sect.…”
mentioning
confidence: 97%